2008
DOI: 10.1080/00986280802377164
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Scholarship of Teaching and Learning via Experimentation

Abstract: In recent years, national policy experts have questioned the overall quality of educational research, and they have suggested that researchers strengthen their scientific methods by maximizing the use of experimental designs. To promote more rigorous methodology, we discuss several new and often-overlooked opportunities for incorporating experimentation into the scholarship of teaching and learning in psychology. Although experiments can be difficult to conduct in educational settings, our methodological sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…All the designs in Table 1 are quasi-experimental, except when the pretest–posttest design with a control group has random assignment. True experiments that allow for causal inferences can sometimes be conducted (LoSchiavo, Shatz, & Poling, 2008); however, they often are not feasible because of curricular constraints and the difficulty of randomly assigning students to control groups (e.g., Nieto & Saiz, 2008). Even when random assignment is not possible, the pretest–posttest with control group design is a powerful tool for studying different forms of instruction when differences in treatment classes and comparison groups are minimized.…”
Section: Guidelines For Effective Assessmentmentioning
confidence: 99%
“…All the designs in Table 1 are quasi-experimental, except when the pretest–posttest design with a control group has random assignment. True experiments that allow for causal inferences can sometimes be conducted (LoSchiavo, Shatz, & Poling, 2008); however, they often are not feasible because of curricular constraints and the difficulty of randomly assigning students to control groups (e.g., Nieto & Saiz, 2008). Even when random assignment is not possible, the pretest–posttest with control group design is a powerful tool for studying different forms of instruction when differences in treatment classes and comparison groups are minimized.…”
Section: Guidelines For Effective Assessmentmentioning
confidence: 99%
“…There is also a general tendency for the learning sciences to focus on similarities between learners while educational research has typically focused on individual differences (Richardson, 1987). Laurillard (1987) argued that this disconnect between the learning sciences and classroom practice needs to be bridged and that practice cannot continue to be based on broad theoretical models but on evidence-based research (LoSchiavo et al, 2008). In less diplomatic terms, Slavin (2008, p. 5) suggested that educational research is fundamentally flawed due to an over-reliance on 'ideology, faddism, politics and marketing.'…”
Section: Self-report Measuresmentioning
confidence: 98%
“…Although some (Tomcho & Foels, 2008) suggest that a pre- and posttest measure is the only valid measure of student learning, applied research is subject to a host of confounding factors (e.g., students are enrolled in multiple courses). LoSchiavo et al (2008) suggest that using scientifically valid experimental designs will become increasingly important. They suggest that evaluating pedagogical innovations by using two groups (i.e., treatment and control) may be the best approach.…”
Section: Developing Student Learning Outcomesmentioning
confidence: 99%
“…Nevertheless, federal legislation continues to increase the emphasis on outcomes as a measure of teaching effectiveness. Resnick (2009) and LoSchiavo, Shatz, and Devereaux (2008) contend that the emphasis on student learning outcomes is related to funding in the Race to the Top initiative and in the future reauthorization of the Elementary and Secondary Education Act. In fact, states must: (a) create assessments that are matched with college readiness, (b) ensure that students have effective teachers, and (c) implement longitudinal measures to assess student progress and teacher effectiveness (Resnick, 2009).…”
mentioning
confidence: 99%